Effects of mutations in Arabidopsis FtsZ1 on plastid division, FtsZ ring formation and positioning, and FtsZ filament morphology in vivo. - David W. Yoder ... [Et al.]; Deena Kadirjan-Kalbach, Bradley J. S. C. Olson, Shin-ya Miyagishima, Stacy L. DeBlasio, Roger P. Hangarter, Katherine W. Osteryoung
Biol
Sala de Colecciones abiertas
Inglés
R11687
Keywords: Arabidopsis; Morfologia de la planta; Mutantes; Artículos de revista